Analisis good corporate governance, pengendalian internal, dan whistleblowing system dan fraud - Sri Wahyuni; Nur Hayati (Universitas Hayam Wuruk Perbanas, 2022)
This research was done as being motivated by the prevailing fraud which commonly has still occured, especially in Islamic banking. The existing fraud cases are carried out by anyone, both internal and external parties. The purpose of this study is to obtain empirical evidence regarding the effect of good corporate governance, internal control, and the whistleblowing system on fraud in Islamic banks registered with the Financial Services Authority (OJK) for the 2018-2020 period. This research is quantitative using secondary data in the form of annual reports of Islamic banking companies for 2018-2020. This sample of 14 companies was taken by using a purposive sampling. They were analyzed using a multiple linear regression analysis with SPSS version 26 software. The results indicate that good corporate governance variable has an effect on fraud. Yet, the internal control variables have no effect on fraud and neither does the whistleblowing system variable on fraud. Good corporate governance, internal control, and the whistleblowing system simultaneously have an effect on fraud. The results of this study have implications for the management of Islamic banking to further strengthen the application of GCG to reduce the level of fraud in Islamic banking.